Study on the Interaction Mechanism between Residual Coal and Mine Water in Goaf of Coal Mine Underground Reservoir - Jiang, Binbin; Zhao, Ze; Liu, Deqian; Cao, Zhiguo; Tang, Jiawei; Wu, Min; Zhang, Haiqin; Li, Peng; Liang, Dingcheng (Sustainability, 2023)
In this paper, the coal pillar dam body of the underground reservoir in Daliuta coal mine, along with the residual coal and the mine water present in the goaf, were taken as research subjects, and a dynamic simulation experiment device was constructed to simulate the actual process of a coal mine underground reservoir (CMUR). The composition and structure of middling coal during the experiment were determined by X-ray diffraction analysis (XRD) and X-ray fluorescence spectrometry (XRF), while changes in ion content in the mine water were assessed through ion chromatography (IC) and inductively coupled plasma emission spectrometry (ICP-OES). Based on both the composition and structure of coal as well as variations in ion concentrations in water, the interaction mechanism between coal and mine water was explored. The results showed that the water–coal interaction primarily arose from the dissolution of minerals, such as rock salt and gypsum, within coal. Additionally, coal samples in mine water exhibited adsorption and precipitation of metal ions, along with cation exchange reaction. Na+ in mine water predominantly originated from the dissolution of rock salt (sodium chloride) in coal, while Ca2+ and SO42− were released through the dissolution of gypsum and other minerals in coal. In the process of the water–coal interaction, Ca2+ in the water body was adsorbed and immobilized by the coal sample, leading to the formation and deposition of CaCO3 on the surface of the coal, thereby increasing the calcite content. These processes collectively contributed to a decrease in the concentration of Ca2+ in the water body. Moreover, the cation exchange reaction occurred between Ca2+ and Mg2+ in mine water and Na+ in the coal sample. The presence of Ca2+ and Mg2+ resulted in their displacement of Na+ within the coal matrix, consequently elevating Na+ concentration in the mine water while reducing both the Ca2+ and Mg2+ concentrations. On this basis, combined with insights from the water–rock interaction, it can be inferred that the adsorption mechanisms involving rocks played a dominant role in the decrease of Ca2+ concentration during the water–rock interactions. Meanwhile, the dissolution processes of minerals both in the water–rock and water–coal interactions predominantly contributed to the increase of Na+ and Cl− concentrations.